Simple, Sensitive and Rapid Ultra-High Performance Liquid Chromatography-Atmospheric Pressure Chemical Ionization Tandem Mass Spectrometry for the Determination of Nicotine and its Nine Metabolites in Human Urine - Fan, Zhong; Liu, Huimin; Xie, Fuwei; Xia, Qiaoling; Wang, Sheng; Chen, Zhiyan; Li, Xiaolan (Asian Journal of Chemistry, 2015)
A simple, sensitive and rapid UHPLC-MS/MS method was developed for the quantication of nicotine and its nine metabolites in human urine. The assay only involves centrifugation and filtration of four times diluted urine, analysis was performed on an Agilent RRHD Eclipse XDB-C18 column (50 mm × 2.1 mm i.d., 1.8 μm, Agilent) using a gradient of 10 mM ammonium acetate, pH 6.8 and methanol as a mobile phase at a flow rate of 200 μL min-1. Separated compounds were determined by atmospheric pressure chemical ionization (APCI) tandem mass spectrometry in the positive ion mode using MRM. The results showed that: recoveries for nicotine and nine of its major metabolites ranged from 93.2-103.8 %; RSD for all the compounds were between 0.9 and 9.5 %. The described method was suitable for determining the nicotine dose in large-scale human bio-monitoring studies.